2018
DOI: 10.3847/1538-4357/aabcc4
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Planetesimal Belt Radius–Stellar Luminosity Relation

Abstract: Resolved observations of millimetre-sized dust, tracing larger planetesimals, have pinpointed the location of 26 Edgeworth-Kuiper belt analogs. We report that a belt's distance R to its host star correlates with the star's luminosity L , following R ∝ L 0.19 with a low intrinsic scatter of ∼17%. Remarkably, our Edgeworth-Kuiper belt in the Solar System and the two CO snow lines imaged in protoplanetary disks lie close to this R-L relation, suggestive of an intrinsic relationship between protoplanetary disk str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(123 citation statements)
references
References 122 publications
11
110
2
Order By: Relevance
“…Let's assume that CO is released at a constant rate Σ + CO , parametrized as a Gaussian centred on r belt = 100 au (belt mid radius) and with FWHM ∆r belt = 50 au. These are arbitrary choices, but overall consistent with the observed distribution of planetesimal disc radii and width around high luminosity stars (Matrà et al 2018b). In Figure 1 the resulting evolution of the CO (left panels) and carbon (middle panels) surface densities and total masses (right panels) are shown for different CO mass input rates and values of α: 0.1 and 0.001.…”
Section: Constant Co Input Ratesupporting
confidence: 71%
See 1 more Smart Citation
“…Let's assume that CO is released at a constant rate Σ + CO , parametrized as a Gaussian centred on r belt = 100 au (belt mid radius) and with FWHM ∆r belt = 50 au. These are arbitrary choices, but overall consistent with the observed distribution of planetesimal disc radii and width around high luminosity stars (Matrà et al 2018b). In Figure 1 the resulting evolution of the CO (left panels) and carbon (middle panels) surface densities and total masses (right panels) are shown for different CO mass input rates and values of α: 0.1 and 0.001.…”
Section: Constant Co Input Ratesupporting
confidence: 71%
“…That study found best-fit parameters A = 5.5 × 10 5 , B = 0.1 and γ = −1.7. We assume the same planetesimal strength relation as before, eccentricities of 0.001 and Γ = 3.1 (the average true to blackbody radius ratio for FGK stars resolved by ALMA, Matrà et al 2018b). Fixing these parameters we have D c = 0.03 km and M mid = 0.16 M ⊕ (vs 0.02 km and 0.5 M ⊕ for A stars), i.e.…”
Section: Solar-type Starsmentioning
confidence: 99%
“…For example, a common assumption is that the mass distribution is log-normal, with the non-detections arising from close-in disks that undergo rapid depletion and so are not detectable in the nearby star population, but it could be that the mass distribution is bimodal, with 80% of stars having no disk. Also, more recently a correlation has been found between planetesimal belt radii determined from high resolution imaging of the sub-mm dust emission and the luminosity of the star (Matrà et al 2018a). If this holds up as more disks are resolved, this would suggest a preferential location for the formation of planetesimal belts that could be linked to ice-lines in the protoplanetary disk for example, which would provide an additional constraint on the population models (as well as significant insight into the origin of the belts).…”
Section: Ab Kbmentioning
confidence: 96%
“…The disk instead lies closer to three other potentially outlying early F/late A disks, which are HR 10 1 10 0 10 1 L (L ) 10 1 10 2 R (au) Figure 6. Radius-Luminosity relation that expands upon the one published in Matrà et al (2018a). The black points represent the published millimeter-resolved belt radii and corresponding belt widths, compared to the host star luminosity.…”
Section: Radius-luminosity Relationshipmentioning
confidence: 77%
“…Understanding why debris disks form at their particular radii from their host stars is key to better understanding the physical mechanisms that create these disks. Matrà et al (2018a) conducted a population study of 26 millimeter-resolved debris disks and found a statistically significant correlation between the host star luminosity and disk radius, which persists when accounting for potential observational biases. Constraining the radii for additional debris disks is the next step to further characterize this radius-luminosity relationship and to further explore other potential correlations.…”
Section: Introductionmentioning
confidence: 97%